Exporting and investment under credit constraints - Kim P. Huynh; Robert J. Petrunia; Joel Rodrigue; Walter Steingress (Bank of Canada, 2023)
We examine the relationship between firms' performance and credit constraints affecting export market entry. The existing research assumes that variation in firms' financial conditions identifies credit constraints. A critical assumption is that financial conditions do not affect real outcomes (performance, exporting, or investment). To relax this assumption, we focus on the direct effect of firms' fundamentals and financial conditions on firms' performance. This approach distinguishes between firms that choose not to export because it is unprofitable from firms that do not export because of binding credit constraints. Our empirical specification allows firms' characteristics to enter both the selection into exporting and return from exporting regressions. The leverage response heterogeneity identifies the presence of credit constraints. Using administrative Canadian firm-level data, our findings show that new exporters (a) increase their productivity, (b) raise their leverage ratio and (c) increase investment. We estimate that 48 percent of Canadian manufacturers face binding credit constraints when deciding whether to enter export markets. Alleviating these constraints would increase aggregate productivity by 0.97-1.04 percentage points.
Keywords: F10; F14; F36; G20; G28; G32; 330; Econometric and statistical methods; Firm Dynamics; International topics; Productivity